The Position of the Van Dading Deed in the Settlement of Joint Property Disputes: Study of Decision 901/Pdt.G/2023/PA. Tmg - Julisa Sistyawan, Dwanda; Abdulah Pakarti, Muhammad Husni; Kurniawan, Lexy Fatharany; Judijanto, Loso; Makkawaru, Zulkifli (Hukum Keluarga Islam IAIN LANGSA, 2024)
This study aims to analyze the use of Van Dading deed in decision 901/Pdt.G/2023/PA. Tmg. Departing from the problem that the Van Dading Deed plays an important role in the settlement of joint property disputes in Indonesia, by providing legal certainty and an efficient settlement mechanism. This research is a doctrinal study with a case approach. This approach is used to analyze court decisions on Van Dading deeds. Legal materials are obtained from court decisions and to strengthen the analysis, this research also uses several scientific articles and research results related to this research issue in order to produce a sharp analysis. This study explores the legal position of Akta Van Dading in the Indonesian legal system, particularly in the context of joint property disputes. This deed, which is produced through mediation, has the same executorial power as a court judgment, ensuring that the agreement reached will be implemented without the need for additional litigation. A case example in this study is Decision 901/Pdt.G/2023/PA.Tmg, which demonstrates the effectiveness of Akta Van Dading in achieving an amicable and binding settlement. Through mediation facilitated by a mediator, the parties to the dispute were able to reach a fair and sustainable agreement. Thus, the Deed of Van Dading not only reduces the court's workload but also encourages faster settlements and lower costs. This research confirms the importance of Akta Van Dading as an essential legal instrument in achieving justice and legal certainty in the settlement of joint property disputes in Indonesia.